A transition game? A comparative analysis of possession usage following turnovers in elite Gaelic football - McNamee, S.; Martin, D.; Bradley, J. (International Journal of Performance Analysis in Sport, 2023)
Almost half of all possessions in elite Gaelic football originate from turnovers. However, understanding of what constitutes a successful possession following a turnover is limited. This study provides the first comprehensive performance profiles for closely contested Senior men`s intercounty knockout championship matches (final score deficit, =6 points), and characterises successful possessions following a turnover. Twenty-nine knockout matches from the 2020 and 2021 All-Ireland Senior Football Championships, including 1,257 possessions following a turnover, were analysed. Statistical differences between winning and losing performances were identified using paired sample t-tests (p = 0.05) and Wilcoxon signed ranked tests (p = 0.05). Binary logistic regression was used to model possession outcome following a turnover. Findings revealed that winning teams were significantly superior to losing teams in securing and retaining possession and demonstrated greater efficiency and productivity in converting possession into scores. Binary logistic regression identified possession duration and the number of attacking phases per possession as the most significant predictors of possession outcome. Prolonged possessions consisting of fewer attacking phases also resulted in a greater score return. These findings enhance existing theoretical understanding of the nature of possessions in Gaelic football and may have practical implications for coaches and performance analysts.